Study of maternal and fetal outcomes in premature rupture of membrane in central rural India - Jaiswal, Arpita A.; Hariharan, C.; Dewani, Deepika K. C. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Premature rupture of membrane is linked to significant maternal prenatal mortalities and morbidity. The maternal and fetal outcomes in PROM is very important to decrease maternal and child mortality and for better management and prevention of complications. Thus, this study aimed to detect the maternal and fetal outcomes in patients with PLROM at tertiary care hospital in central rural India. Methods: This prospective study was conducted in Department of obstetrics & Gynecology, in a tertiary care institute located in central India, over a period of 18 months. 210 patients were diagnosed with PLROM and all of them were included in the study. The data of these women were collected using a checklist based on registration books. Results: The rate of maternal morbidity was 26%, commonest cause was clinical chorioamnionitis (11.9%) followed by febrile illness seen in 10.5%. No maternal mortality was seen in the study. Perinatal morbidity was seen in 30% of cases. Clinical early onset neonatal infection was the commonest cause for perinatal morbidity noticed in 23.8% of cases (50 out of 210). Perinatal mortality observed was 1.43% (3 out of 210). Birth asphyxia being the commonest cases of mortality. Conclusions: Major maternal morbidity is chorioamnionitis (11.9%). Major perinatal morbidity observed is early onset neonatal infection (24%).